Risk of Hypertension and Diabetes in Patients with Cholecystectomy - HUMAIRA SAMI ULLAH, ABDUL MATIN QAISAR, NIDA, NAZIA AZAM YOUSFANI, MUHAMMAD YAMEEN MANGAN, HUMA SAEED KHAN, (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Although cholecystectomy is often considered a straightforward and harmless surgery with minimal long-term impact on a patient's health, it can result in significant increase in metabolic diseases. Objective: To determine the risk of hypertension and diabetes in patients with cholecystectomy. Study Design: Retrospective cohort study Place and Duration of Study: Medical unit 2, Department of General Medicine, Bolan Medical Complex Hospital, Quetta, from 1st January 2016 to 31st December 2020. Methodology: One hundred cases that underwent cholecystectomy within last 5 years were compared with 100 controls. All patients who had undergone cholecystectomy and were ≥35 years of age, were included. The patients in the control group were compared with cholecystectomy group patients in terms of their demographics, body mass index, systolic and diastolic blood pressure, blood glucose levels, cholesterol level, extent of physical activity and mortality index. Results: The value of systolic blood pressure and cholesterol tends to increase in the further mean 3.21 (95% confidence interval 0.21 to 6.21), mean8.92 (95% confidence interval 15.09to 2.73) in control group when compared with cholecystectomy group patients mean 1.52 (95% confidence interval 1.51 to 4.52) and mean 14.15 (95% confidence of interval 20.32 to 7.97) while body mass index showed a greater increase in cholecystectomy patients mean 1.52(95% confidence interval 1.51 to 4.52)as compared to control as mean 0.01 (95% confidence interval 0.25 to 0.24). Conclusion: There is a slight risk of rise in fasting blood glucose levels in patients who have undergone cholecystectomy. Keywords: Cholecystectomy, Gallbladder, Hypertension, Diabetes mellitus.